Carbon nanotubes-cellulose acetate nanocomposites: membranes for water desalination - El Badawi, Nouran Ashraf (AUC Knowledge Fountain, 2013)
Cellulose acetate (CA) (Mw = 52,000 Da) membranes were prepared by phase inversion (PI) using acetone as a solvent. Investigation of different preparation conditions were carried out. The effect of membrane casting thickness, CA content, coagulation bath temperature (PI temperature), solvent evaporation, addition of a non-solvent (deionized water), and addition of multi-walled carbon nanotubes (MWCNTs) on membrane morphology and performance (permeation rates and salt rejection rates) were investigated. Membranes morphologies were studied using scanning electron microscopy (SEM). Membranes permeations rates and salt rejection rates were investigated using 1000 ppm NaCl solution. Optimum conditions for developing a CA based nanocomposites were attained, entailing 15 wt% CA content, 20 wt% H2O non-solvent additive, low functionalized CNTs contents (0.0005, 0.005, and 0.01 wt%), PI at room temperature, and sonication time for CNTs proper dispersion less than 1 minute. MWCNTs/CA nanocomposites membranes were prepared. MWCNTs were first functionalized by oxidation purification in a strong acidic medium to enhance their dispersion within the polymer matrix, and the success of the functionalization of MWCNTs was characterized using Fourier transform infrared (FTIR) spectroscopy. The nanocomposites morphologies were characterized by several methods by SEM and nitrogen adsorption. SEM images showed large networks of MWCNTs, randomly oriented and properly dispersed, with a significant decrease in the number of macrovoids development with CNT content increase at the same final thickness of the nanocomposites. This was verified by analysis of pore sizes (differential volumes and surface areas), which were found to decrease with the increase in CNT content. Nanocomposites permeations rates and salt rejection rates were investigated using 1000 ppm NaCl solution, and it was found that permeation improved significantly with the addition of CNTs, with the improvement being highest for lowest CNT content. Salt rejection was found to decrease with the presence of CNTs. However the decrease was minimal for low CNT contents. In this respect, it was possible to prepare CA-CNT nanocomposite membranes with improved permeation of 19.57 L/m2h, together with a minimal decrease of salt retention performance of 69.4% at 24 bars operating pressure. The membranes performance could be explained by membrane morphology (surface areas and porosity).